Question Answering on Quantum Computers. - Draper, Thomas (Journal of the Utah Academy of Sciences, Arts & Letters, 2023)
The first quantum algorithm for processing language was run in 2020, sparking great research interest in the field. This article introduces the background of quantum computation as well as the relationship between quantum theory and the theory of natural language, intending to make the topic accessible to an audience familiar with linear algebra. No knowledge of linguistics or quantum computing is assumed. This paper illustrates the method of converting sentences to quantum circuits. The algorithm is implemented in Python to parse sentences and convert them to parameterized quantum circuits. IBM's Qiskit framework is used to build these circuits and evaluate them using simulators and actual quantum hardware. The circuit's parameters are optimized using a gradient-free machine learning method, which allows accurate predictions for the truth of simple sentences.